Integrated approach to small business development in Ukraine. Theory, practice and ways of improvement - Mykhailo Pyvovarov (Cхід, 2013)
The study presents the results of research of how major institutions influence small business in Ukraine. Particular attention is paid to the analysis of Amendment 5,6 to the Tax Code of Ukraine on a simplified tax system. The study also includes analysis, calculations and offers ways to improve the situation.